Keberlanjutan Inovasi Alumni Diklat Kepemimpinan Tingkat III Dan IV Di Provinsi Sulawesi Barat - Milawaty Milawaty (Jurnal Transformasi Administrasi, 2017)
Bureaucracy reform has provided vast space for ministries, institutions, local governments, and even individuals to innovate in governance. Various laws-related innovation has emphasized the importance and urgency of the government's role in supporting the growth of innovation. National Institute of Public Administration (LAN) since 2014 began to implement a new curriculum on education sistem nationally. Through this, it is hoped that a bureaucratic leader will emerge with the ability to overcome problems and various strategic national issues through innovative methods and work processes in it. This study aims to see the sustainability innovation of Leadership Education and Training Alumni in West Sulawesi Province. The number of informants was 20 people, consisting of 11 alumni, and 9 mentors and effective teams. The data were analyzed qualitatively through data collection, data reduction, display data, and conclusions. The results showed: (1) Only five alumni were able to continue their innovation. Six other alumni had to stop. (2) For alumni who succeeded in continuing their innovation, the supporting factors of sustainability of alumni innovation are policy, commitment of leader, peer / stakeholder, infrastructure and budget, while limiting factor is limited resources, lack of response of data request, minimize failures, and internet network. (3) For alumni who have not succeeded in continuing their innovation, the inhibiting factors are policy, institutional reform plan, leadership commitment, infrastructure, budget, mutation, stakeholder, socialization of innovation, and internet network